Entrepreneurial Potential of Restaurant and Cafe Organic Waste - Hanum, Latifah; Sulastri, Sulastri; Ramli, Ichwana; Zatya, Ismi (Jurnal Pengabdian Bakti Akademisi, 2025)
Ecoenzyme is a multifunctional liquid derived from the utilization of fermented household organic waste. This dedication aims to provide understanding to partners to utilize the remaining vegetable waste and fruit skins into ecoenzymes which are then further processed into various useful products. The service begins with conducting a survey of organic waste found in restaurants and catering. Then sort out the wastes that can be used to produce ecoenzymes. This method of service is by providing training, mentoring the production and marketing of the products produced. After dedication, Ecoenzyme derivative products were obtained in the form of hand soap, dish soap and floor cleaner. Currently, these Products have been given a trademark name, composition, and description of the date of production